Occurrence of five species of Eriophyoid mites (Acari: Eriophyoidea) and their nature of infestation on tropical plants from northern Districts of West Bengal, India (Bangladesh Journal of Zoology, 2023)
During the general surveys for eriophyoid mites in two districts namely Malda and Dakshin Dinajpur of West Bengal, India, five eriophyoid mites namely Aceria ficus (Cotte), Aceria granati (Canestrini & Massalongo), Aceria mauritianae Amrine & Stasny, Aceria nerii Channabasavanna, and Aceria lalbaghi Amrine & Stasny, were collected from four tropical plants. The host association, relationship with the host plants and their nature of damage, climatic condition of the study area, vegetative patterns of the study area and a taxonomic key to the species are provided in this article.Bangladesh J. Zool. 51(1): 55-70, 2023